Little hands celebrate America! : learning about the U.S.A through crafts & activities - Hauser Jill Frankel 1950 (Nashville, Tenn. : Williamson Pub., 2004)
Easy crafts and activities like making crowns, Navajo bracelets, and a patchwork quilt, help introduce America's history, geography, symbols, and people.
Keywords: United States -- Juvenile literature; Creative activities and seat work -- Juvenile literature; United States -- Study and teaching Preschool -- Activity programs; United States -- Study and teaching Primary -- Activity programs; United States; Handicraft